2021
DOI: 10.2217/fon-2020-1264
|View full text |Cite
|
Sign up to set email alerts
|

CDK4/6 Inhibitors in HR+/HER2- Advanced/metastatic Breast Cancer: A Systematic Literature Review of Real-World Evidence Studies

Abstract: Background: This review aims to qualitatively summarize the published real-world evidence (RWE) for CDK4/6 inhibitors (CDK4/6i) approved for treating HR+, HER2-negative advanced/metastatic breast cancer (HR+/HER2- a/mBC). Materials & methods: A systematic literature review was conducted to identify RWE studies of CDK4/6i in HR+/HER2- a/mBC published from 2015 to 2019. Results: This review identified 114 studies, of which 85 were only presented at scientific conferences. Most RWE studies investigated palboc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 70 publications
3
27
0
3
Order By: Relevance
“…There is limited information, however, regarding tumor response to palbociclib plus an aromatase inhibitor (AI) compared with an AI alone in real-world clinical practice [24]. A multi-country retrospective medical chart review of patients with HR+/HER2-advanced breast cancer (ABC) or MBC, who received palbociclib in combination with either an AI or fulvestrant in real-world clinical practice, reported a real-world objective response rate (based on physicians' assessments) of 79.5% in the USA and 66% in Argentina [19].…”
Section: Introductionmentioning
confidence: 99%
“…There is limited information, however, regarding tumor response to palbociclib plus an aromatase inhibitor (AI) compared with an AI alone in real-world clinical practice [24]. A multi-country retrospective medical chart review of patients with HR+/HER2-advanced breast cancer (ABC) or MBC, who received palbociclib in combination with either an AI or fulvestrant in real-world clinical practice, reported a real-world objective response rate (based on physicians' assessments) of 79.5% in the USA and 66% in Argentina [19].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials demonstrated the efficacy of palbociclib plus fulvestrant, however real-world data may provide valuable information on the long-term effectiveness and safety of medicines, which is particularly relevant for patients, clinicians and third-party payers. Although some evidence on the effectiveness of this association already exists, the great majority is from single-centre/healthcare institution studies, having limited sample sizes and/or short follow-up times [ 9 , 10 ]. Consequently, the generalizability of results may be considerably reduced, highlighing the need for additional evidence arising from multicentre/population-based studies with longer follow-up periods.…”
Section: Introductionmentioning
confidence: 99%
“…We used the MIMA system to perform a small-scale screening study in which we quantitatively assessed the responses to five FDA approved targeted therapies and two chemotherapeutic agents with distinct modes of action. The targeted drug were the poly (adenosine diphosphate [ADP]) ribose polymerase (PARP) inhibitor, olaparib (Lord and Ashworth, 2017); the multi-kinase vascular endothelial growth factor receptor (VEGFR)-1/2/3 inhibitor, lenvatinib (Kato et al, 2019); the cyclin dependent kinase (CDK)-4/6 inhibitor, palbociclib (Harbeck et al, 2021); the B-cell lymphoma (BCL)-2 inhibitor, venetoclax (Montero and Letai, 2018); and the pan-histone-deacetylase (HDAC) inhibitor, panobinostat (Atadja, 2009). The chemotherapeutic drugs were the DNA-intercalating agent, doxorubicin and the microtubule poison, paclitaxel, which are often used in first line therapy for breast cancer (Cardoso et al, 2018; Kumar et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Genomic screening approaches have supported such tumor-intrinsic aspects of precision medicine, leading to matching of genomic aberrations with specific targeted agents (Li et al, 2021). In breast cancer, treatments targeting tumors that depend on estrogen receptor (ER) signaling, aberrant signaling resulting from human epidermal growth factor receptor 2 (HER2) amplification and/or over expression, CDK4/6 signaling and defects in DNA repair in triple negative breast cancer (TNBC) have been particularly effective (Bettaieb et al, 2017; Hanker et al, 2020; Harbeck et al, 2021; Lord and Ashworth, 2017). Unfortunately, these treatments are not uniformly effective even in primary tumors carrying the target and are usually only transiently effective in metastatic disease (Brady et al, 2017; Janiszewska et al, 2021; Jeselsohn et al, 2017).…”
Section: Introductionmentioning
confidence: 99%